2011
DOI: 10.1371/journal.pone.0028244
|View full text |Cite
|
Sign up to set email alerts
|

Population Size Influences Amphibian Detection Probability: Implications for Biodiversity Monitoring Programs

Abstract: Monitoring is an integral part of species conservation. Monitoring programs must take imperfect detection of species into account in order to be reliable. Theory suggests that detection probability may be determined by population size but this relationship has not yet been assessed empirically. Population size is particularly important because it may induce heterogeneity in detection probability and thereby cause bias in estimates of biodiversity. We used a site occupancy model to analyse data from a volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…This relationship between detection and pond area may be due to a link between pond area and the abundance of each species. This conclusion would be in accordance with previous studies that have shown that abundance is one of the most determinant factors in detection probability (Mackenzie et al 2002;Royle and Nichols 2003), especially in amphibians (Dodd and Dorazio 2004;Tanadini and Schmidt 2011). Secondly, this approach revealed that the presence of PR negatively influenced BV detection, whereas the occurrence of BV had a positive effect on PR detection.…”
Section: Discussionsupporting
confidence: 92%
“…This relationship between detection and pond area may be due to a link between pond area and the abundance of each species. This conclusion would be in accordance with previous studies that have shown that abundance is one of the most determinant factors in detection probability (Mackenzie et al 2002;Royle and Nichols 2003), especially in amphibians (Dodd and Dorazio 2004;Tanadini and Schmidt 2011). Secondly, this approach revealed that the presence of PR negatively influenced BV detection, whereas the occurrence of BV had a positive effect on PR detection.…”
Section: Discussionsupporting
confidence: 92%
“…We believe that occasional detections of these dispersing individuals is the cause of our unexpectedly-low detection probabilities. The consequences of false-positive errors are most extreme for rare species (Miller et al, 2011), which may also be hard to detect due to low abundances (McCarthy et al, 2013;Tanadini & Schmidt, 2011). The usual approach "pond = population" may be wrong because within-season movements between sites appear to be common in amphibians (Kopecky, Vojar, & Denoel, 2010;Petranka et al, 2004;Schmidt, 2005;Tournier, Besnard, Tournier, & Cayuela, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When surveyed, each site was visited on three occasions during predefined time windows coinciding with the amphibian breeding season. Further information on the survey protocol can be found in Tanadini and Schmidt (2011) and Roth, BĂŒhler, and Amrhein (2016). Volunteers were asked to record complete checklists; we therefore were able to infer non-observation of species not explicitly reported during a visit (KĂ©ry, Gardner, & Monnerat, 2010).…”
Section: Aargau Monitoring Programmentioning
confidence: 99%
“…The design recommendations are based on the probability of detection and occupancy rates estimated in this pilot study and should therefore be re-evaluated as these change. Abundance-induced heterogeneity in detection probability can induce bias in the occupancy estimator [37]. If such heterogeneity is suspected, a model that accounts for it would be more appropriate.…”
Section: Discussionmentioning
confidence: 99%